SURVEI SEROLOGIS TOXOPLASMOSIS PADA TERNAK SAPI DI KABUPATEN PRINGSEWU MENGGUNAKAN METODE TOXOPLASMA MODIFIED AGGLUTINATION TEST (To-MAT) - B., Galang; R., Emantis; P., Gina Dania; S., Endah (JURNAL ILMIAH PETERNAKAN TERPADU, 2019)
The cattle population in Lampung Province has a relatively high number when compared to several other provinces. Pringsewu is one of the districts in Lampung Province having the supplier potential of beef in Lampung. The higher the population and production, could cause a potential infection of toxoplasmosis to livestock and human. So far the prevalence of toxoplasmosis in Pringsewu District. This study was conducted to determine the level of toxoplasmosis infection in cattle in Pringsewu district. This study used the To-MAT (Toxoplasma Modified Agglutination Test) method to test Toxoplasma gondii infection in blood of cows samples. The result of the study found that at a chronic level there were 23/24 cows positively infected with T.gondii. Whereas in acute level there are 8/24 cows positively infected with T. gondii. In general, the prevalence of toxoplasmosis is 95.8%. Keywords : Toxoplasmosis, Cow, To-MAT (Toxoplasma Modified Agglutination Test) method, Infection